2018
DOI: 10.18293/seke2018-153
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing The Impact Of Feedback In GitHub On The Software Developer's Mood

Abstract: Software development depends on cooperation between people, and the way it works can define the future of the software project. Developers emotions affect their productivity and way they work, yet there is little information about how developers can influence the mood of each other. As a first step toward understanding how feedback may affect the developers' sentiment, this paper analyzes the mood variations on more than 78k pull requests and 268k pull comments on GitHub. We found that in 31.16% of the cases t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Similarly, a very large study found that negative feedback has a significant impact on developers' attitude [215]. Developers might not contribute again after receiving negative feedback and this impact increases with the size of the project [215]. 4.2.4 CRP -Modern code review process properties.…”
Section: Mcr Themes and Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a very large study found that negative feedback has a significant impact on developers' attitude [215]. Developers might not contribute again after receiving negative feedback and this impact increases with the size of the project [215]. 4.2.4 CRP -Modern code review process properties.…”
Section: Mcr Themes and Contributionsmentioning
confidence: 99%
“…Specific feedback such as "Incomplete fix" and "Suboptimal solution" might encourage contributors to continue to work in open source software projects [185]. Similarly, a very large study found that negative feedback has a significant impact on developers' attitude [215]. Developers might not contribute again after receiving negative feedback, and this impact increases with the size of the project [215].…”
Section: Impact Of Code Reviews On Product Quality and Human Aspects ...mentioning
confidence: 99%
“…Team Performance [65] Socio-Technical modern code review metrics Identification of bugs/warning/vulnerabilities [44] Reviewers' path development experience Identification of bugs/warning/vulnerabilities [79] Feedback Developers' sentiment [64] quality [7,43,46,66,76], human memory [39,70], chances in inducing bug fixes [7], if-statements and change requests [59,83,84], and the identification of bugs/warning/vulnerabilities [12,54].…”
Section: Impact And/or Outcomementioning
confidence: 99%